Development Of Islamic Religious Education Materials As Student Deradicalization Effort At SMK 17 Seyegan Sleman - Ari Reza Wicaksono (AIUA Journal of Islamic Education, 2020)
Recently, the discussion about religious radicalism is getting hotter, this is due to the increasing prevalence of intolerant groups in society. Preventive efforts are an ideal step to prevent the development of such understandings and movements. One of the efforts that can be done is to provide the right understanding of religion to students. Therefore, the development of deradicalization material in Islamic Religious Education is urgent to be carried out. The purpose of this study is to provide an overview of the procedures for developing Islamic Religious Education materials, especially deradicalization. This type of research is a qualitative field research. The data were obtained from interviews and documentation, then the data were analyzed using descriptive analysis techniques. The results of the study there are six considerations that are used as the basis for PAI teachers at SMK 17 Seyegan to develop deradicalization materials. Other results show that there are ten learning materials in grades X, XI, and XII that were developed by teachers to prevent the development of radicalism in students.